Rural Transformation in the Post Liberalization Period in Gujarat Economic and Social Consequences - Mehta, Niti (Springer Singapore, 2018)
The book examines the pattern of non-farm development at the national level and identifies the correlates and determinants of occupational diversification for the major states. It is one of the few studies that unravels the dynamic processes associated with growth and development at the sub-national level; wherein it elucidates changes in rural employment pattern and its implications for urban growth. The book fills a crucial gap in current research, notably, an understanding of conditions that enable large villages to assume an urban character. By providing micro-level study of census towns to capture the nuances of the dynamic situation in the countryside, the book would offer useful insights and provide reference material on the social and economic impacts of urban growth, thereby satisfying the needs of students, researchers and practitioners of regional economics, rural development, and sustainable urbanization. The book is the outcome of financial support received under the Research Programme Scheme of the Indian Council of Social Science Research (ICSSR), New Delhi, India.